2021
DOI: 10.3389/fmolb.2021.655570
|View full text |Cite
|
Sign up to set email alerts
|

The Adjuvant Effects on Vaccine and the Immunomodulatory Mechanisms of Polysaccharides From Traditional Chinese Medicine

Abstract: Vaccination is still the most successful strategy to prevent and control the spread of infectious diseases by generating an adequate protective immune response. However, vaccines composed of antigens alone can only stimulate weak immunogenicity to prevent infection in many cases. Adjuvant can enhance the immunogenicity of the antigens. Therefore, adjuvant is urgently needed to strengthen the immune response of the vaccines. An ideal adjuvant should be safe, cheap, biodegradable and biologically inert. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…IL-1β and TNF-α are released by multiple signaling transduction pathways, including TLRs, which are widely expressed on the surface of macrophages (Roeder et al, 2004;Wang et al, 2021). TLRs are the most important ones of PRRs, which form the cornerstone of the innate immune response (El-Zayat et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-1β and TNF-α are released by multiple signaling transduction pathways, including TLRs, which are widely expressed on the surface of macrophages (Roeder et al, 2004;Wang et al, 2021). TLRs are the most important ones of PRRs, which form the cornerstone of the innate immune response (El-Zayat et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…TLRs are the most important ones of PRRs, which form the cornerstone of the innate immune response (El-Zayat et al, 2019). Among the members of TLRs, TLR2 and TLR4 can bind polysaccharide ligands, activating the downstream signaling axes (Wang et al, 2021). CD14, mainly produced by monocytes and macrophages, recognizes and binds various structures and subsequently transfers them to TLRs (Allam et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this observation, they proposed that the inhibitory effects of APS on migration of CD4 + CD25 + Treg cells is correlated with the CXCR4/CXCL12 signaling pathway [ 88 ]. Moreover, APS has also been shown to boost the phagocytic capacity of peritoneal macrophages and the proliferation of splenic lymphocytes; increase the serum antibody titters and the production of cytokines such as IL-4 and IL-10, CD40, CD86 in dendritic cells; and promote the maturation of dendritic cells and the transformation rate of peripheral blood neutrophils and lymphocytes [ 89 ].…”
Section: Immunomodulatory Functions Of Astragalus and Shiitake In Tumour Immune Microenvironmentmentioning
confidence: 99%
“…Many studies have shown that polysaccharides used in Chinese medicine have attracted interest in the eld of natural macromolecules because of their signi cant biological activities, which include antitumor (5), antioxidant(6) and anticoagulant activities (7), and treatment applications for ischemiareperfusion injury(8), liver protection (9), viral infections (10), control of blood lipids (11), control of blood pressure (12) and immune regulation (13). Scutellaria barbata D. Don is a plant of the family Lamiaceae (14), is listed in the 2015 edition of the Chinese Pharmacopoeia and has the unique effects of clearing away heat and toxic material, diuresis and detumescence.…”
Section: Introductionmentioning
confidence: 99%